Construction of Stable Donor–Acceptor Type Covalent Organic Frameworks as Functional Platform for Effective Perovskite Solar Cell Enhancement - Li, Zhongping; Zhang, Zhenwei; Nie, Riming; Li, Chunzhi; Sun, Qikun; Shi, Wei; Chu, Weicun; Long, Yuyang; Li, He; Liu, Xiaoming (Advanced functional materials, 2022)
Covalent organic frameworks (COFs) as a new class of crystalline, porous materials have attracted extensive attention in the fields of photocatalytic and photovoltaic applications. Generally, donor–acceptor (DA) structures play an important role in the charge separation efficiency of solar cells. In this study, two DA‐COFs with high crystallinity, good porosity, and excellent stability are incorporated into the FAPbI3 layer of perovskite solar cells. This addition of DA‐COFs reduces the defect concentration and shallows the defect state. The donor–acceptor system in COFs also possesses strong charge‐transfer pathway, which strongly prevents charge recombination to afford more efficient charge separation efficiency. The highest power‐conversion efficiency of perovskite solar cells constructed with DA‐COFs is 23.19% with excellent humidity stability of the solar cells. Therefore, this work provides a pathway for using DA‐COFs to fabricate perovskite solar cells with higher efficiency and stability. Two donor–acceptor (DA) covalent organic frameworks (COFs) show high crystallinity, good porosity, and excellent stability, which are incorporated into the FAPbI3 layer of perovskite solar cells. The highest power‐conversion efficiency observed for perovskite solar cells constructed with DA‐COFs is 23.19% with excellent humidity stability, which provides a pathway for using DA‐COFs to fabricate perovskite solar cells with high efficiency and stability.